Proceedings of the 11th European Conference on Thermoelectrics ] : ECT 2013 - Tang, Francois; Amaldi, Andrea (Springer International Publishing, 2014)
The Proceedings of the 11th European Conference on Thermoelectrics contains manuscripts from leading experts on topics spanning from material processing to applications in the field of thermoelectrics. The selected manuscripts also describe recent developments on measurement systems of thermoelectric properties, and the design and modelling of thermoelectric generators.